Stres Kerja Ditinjau dari Persepsi Dukungan Organisasi pada Karyawan - Hartini, Sri; Mutia Alya Mukhbita; Kheren Febriana Br Bangun; Fransiska Permatasari Nainggolan; Qorry Rizqina Hasibuan; Raisa Alfita Husna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study was conducted to explore the relationship between work stress and organizational support at PT. Daya Adicipta Wihaya (Daya Daihatsu Langkat) on 161 employees. Two scales were used: a work stress scale with 22 valid items and an organizational support scale (Perceived Organizational Support) also with 22 valid items. The results of the analysis showed that 50.3% of employees were in the low work stress category, while 91.3% felt high organizational support. The correlation test using Pearson Product Moment showed a moderate negative relationship between work stress and organizational support, with a coefficient of -0.581 and a significance of 0.000 (p <0.05). This means that the higher the organizational support, the lower the level of work stress experienced by employees. R² of 0.234 indicates that 23.4% of work stress variability is influenced by perceived organizational support, while 76.6% is influenced by other factors. These findings indicate that strong organizational support can help employees cope better with stress, increase job satisfaction, and create a positive work environment. These results are in line with previous studies that emphasize the importance of organizational support in reducing work stress and increasing productivity. Keywords: Organization, Correlation test, Work stress